Functional properties of frozen dairy systems and their relation to ice cream texture: a review - Pintor-Jardines, María Aurora (Universidad Autónoma de Tamaulipas, 2013)
Ice cream is a colloidal dispersion that consists of one disperse phase, immersed in a continuous phase of high viscosity. The disperse phase has three main components that provide its structure: air bubbles, ice crystals and emulsified and dispersed fat globules. The liquid phase is, in turn, composed by sugar, milk protein and hydrocolloids dissolved in non-frozen water. This paper reviews the effect of the functional properties of the different ingredients on the stability of this complex mix, and on the formation of the tridimensional structure of the disperse phase, influencing the microscopic size and dispersion of the air bubbles, the fat globules and the ice crystals that macroscopically give the creamy taste of ice cream.